THE INCIDENCE OF JUVENILE MYOCLONIC EPILEPSY AND ANALYSIS OF ITS THERAPY ACCORDING TO THE DATA OF THE “EPICENTER” (VOLGOGRAD) - O. V. Belyaev; E. A. Volkova (Русский журнал детской неврологии)
Juvenile myoclonic epilepsy (JME) (Janz syndrome) is a form of idiopathic generalized epilepsy (IGE) of adolescence, which is characterized by massive bilateral myoclonic seizures occurring predominantly in the arms on awakening from sleep. A Proposed Diagnostic Scheme for People with Epileptic Seizures and with Epilepsy (2001) refers JME to a group of IGE with a variable phenotype. JME is one of the most com- mon forms of epilepsy (7 % among all forms of epilepsy and 27 % among its all idiopathic forms). The authors describe the history of epilepsy, the specific features of the course of the disease, its clinical manifestations, the characteristic types of seizures, and approaches to diagnosis and therapy. They also proposed the results of their investigation, the aim of study were epidemiological pattern of JME and the specific features of its therapy and remission in the Volgograd Region. The investigation showed that 83 % of the patents with JME in the Volgograd Region could achieve remission with medical treatment, as shown by the EpiCenter. Valproates are the drugs of choice (remission was achieved in 92 %). The most common combination was levetiracetam and valproate (71 % remission). Complete clinical and electroencephalographic remission of JME was achieved in 41 % of cases, valproates therewith remain to have benefits too (58 % remission).